Identification of nonabsorbable inhibitors of the scavenger receptor-BI (SR-BI) for tissue-specific administration. Issue 8 (15th April 2016) - Sparks, Steven M.; Zhou, Huiqiang; Generaux, Claudia; Harston, Lindsey; Moncol, David; Jayawickreme, Channa; Parham, Janet; Condreay, Patrick; Rimele, Thomas
Graphical abstract: Abstract: The identification of a low-permeability scavenger receptor BI (SR-BI) inhibitor starting from the ITX-5061 template is described. Structure–activity and structure–permeability relationships were assessed for analogs leading to the identification of compound8 as a potent and nonabsorbable SR-BI inhibitor.